FLOWER METAPHOR INSPIRATION IN FINE ARTS - Putra, Anak Agung Ramanda; Mudana, I Wayan; Bendi Yudha, I Made (Program Studi Seni Murni ISI Bali, 2025)
This report is written to explain the creation of a work of art with the theme